Constraining nitrification by intermittent aeration to achieve methane-driven ammonia recovery of the mainstream anaerobic effluent. (1st October 2021) - Li, Xin; Lu, Yongze; Chen, Yue; Zhu, Guangcan; Zeng, Raymond Jianxiong
Abstract: Mainstream anaerobic treatment has the potential to capture organic energy, and represents a sustainable development trend, but with the problems of low biogas quality and dissolved methane emissions. In this study, methane-driven ammonia recovery of anaerobic effluent was proposed. A 380-day long-term experiment, which was divided into four phases according to different aeration modes, was conducted. The ammonia conversion and microbial characteristics shows that ammonia oxidizing bacteria (AOB) were constrained during Phases 2 (DO: <0.2 mg L −1 ) and 4 (DO: 0.1–1.6 mg L −1 ), and were active during Phase 3 (DO: 2–4 mg L −1 ). During phase 4, when the intermittent aeration was used, the total nitrogen removal rate was higher than during Phases 2 and 3, and nearly 100% ammonia was removed. Methylomonas, a genus of methane oxidizing bacteria (MOB), was enriched during Phase 4. The serum bottle experiment confirmed that the ammonia removal occurred through the MOB assimilation. The protein content in the CH4 -added group was 35.5%, which was higher than in the group without CH4 (23.3%). The powerful ammonia assimilation and protein synthesis capabilities of MOB give a meaning to the anaerobic effluent for ammonia recovery and protein production. Intermittent aeration could be used to constrain AOB and improve ammonia recovery efficiency. Graphical abstract: Image 1 Highlights: MOB were more competitive than AOB under the low oxygen concentration. Intermittent aeration was used to avoid AOB growth and maintain MOB activity. Ammonia recovery occurred through MOB assimilation for protein synthesis. Activated AOB may inhibit certain genus of MOB under sufficient oxygen.